تأثير الطرق الصوفية على العملية السياسية في السودان - Rajab Mohamed Eshtiba
This study aims to highlight the impact of the Sufi orders in the political process in Sudan by revealing aspects of this effect. Where the Sufi orders in Sudan played an active role in the aspects of life in general,and the political scene in particular.Based on that,the problem of the study is embodied in the question: to what extent the Sufi orders affect on the political process in the Sudan.In this contex,the study examines the motives which resulted in the entry of the Sufi orders,as an influential actor, in the formation of the political field in Sudan. Therefore,studying the political role of the Sufi Orders stems from that it classified within the political pressure groups.The study applied both introspective and analytical approach for the diagnosis of the role of Sufi orders in the political life in the Sudan. The study applied both inductive and analytical method for diagnosing of role of Sufi orders in the political life in the Sudan. Accordingly, the researcher analysed the documents and relevant information. The study found that the Sufi orders in the Islamic world, asa well as its social and religious role, played an influential role in the political process.Where their followers represented a source of support to political parties. Thus, the Sufi orders contributed to formation of religious and political identity of the Sudan. In this regard, both the group Khatmiyya and Ansar represented the first religious currents that have entered the political arena, and their role continued in participating in the political process in all political epochs that ruled the country.Therefore, these two groups gained attention from systems of governance in order to ensure the political stability.